Hadith #3269 - Sunan Abi Dawud - Abdur Rahman bin Abi Bakr; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري (Sunan Abi Dawud)
“He did not inform him.”
Grade: Sahih

Hadith #3270 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abdur Rahman bin Abi Bakr; Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Salm bin Nwh bin Aby سالم بن نوح بن أبي (Sunan Abi Dawud)
Some guests visited us, and Abu Bakr was conversing with the Messenger of Allah (ﷺ) at night. He (Abu Bakr) said: I will not return to you until you are free from their entertainment and serving them food. So he brought them food, but they said: We shall not eat it until Abu Bakr comes (back). Abu Bakr then came and asked: What did your guest do? Are you free from their entertainment ? They said: No. I said: I brought them food, but they refused and said: We swear by Allah, we shall not take i
Grade: Sahih

Hadith #934 - Jami' al-Tirmidhi - Abdur Rahman bin Abi Bakr; Amr bin Aws bin Abi Aws عمرو بن أوس بن أبي أوس; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Muhammad bin Yahya bin Abi 'Umar محمد بن يحيى بن أبي عمر العدني; Sufyan bin 'Uyaynah سفيان بن عيينة; Yahya bin Musa Khat يحيى بن موسى خت (Jami' al-Tirmidhi)
“Umrah to ‘Umrah atones for the sins between them, and for A1-Hajj Al-Mabrur there is no reward except Paradise.”
Grade:

Hadith #1016 - Jami' al-Tirmidhi - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Abdur Rahman bin Abi Bakr; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Aisha bint Abi Bakr; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Jami' al-Tirmidhi)
“The Messenger of Allah came to Hamza on the Day of Uhud, he stood over him and saw that he had been mutilated. He said: Had it not been that Safiyyah would be distressed, then I would have left him to be eaten by the beasts until he was gathered on the Day of Judgment from their stomachs.” He said: “Then he called for a Namirah to shroud him with. When it was extended over his head, it left his feet exposed, and when it was extended over his feet, it left his head exposed.” He said: “
Grade:

Hadith #1695 - Sunan Ibn Majah - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Abdur Rahman bin Abi Bakr; Aisha bint Abi Bakr; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan Ibn Majah)
The Messenger of Allah forbade on the Day of Khaibar, the temporary marriage of women and (he forbade) the flesh of domestic donkeys.
Grade:

Hadith #3111 - Sunan Ibn Majah - Abdur Rahman bin Abi Bakr; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amr bin Aws bin Abi Aws عمرو بن أوس بن أبي أوس; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“Whoever drinks wine and gets drunk, his prayer will not be accepted for forty days, and if he dies he will enter Hell, but if he repents, Allah will accept his repentance. If he drinks wine again and gets drunk, his prayer will not be accepted for forty days, and if he dies he will enter Hell, but if he repents, Allah will accept his repentance. If he drinks wine again and gets drunk, his prayer will not be accepted for forty days, and if he dies he will enter Hell, but if he repents Allah wi
Grade: